Hot Work Tool Steel Processed by Laser Powder Bed Fusion: A Review on Most Relevant Influencing Factors. Issue 7 (16th July 2021) - Wu, Liang; Das, Suvajeet; Gridin, Witalij; Leuders, Stefan; Kahlert, Moritz; Vollmer, Malte; Niendorf, Thomas
Abstract : Additive manufacturing is highly attractive for advanced tooling. Numerous steels are considered for realization of superior tool designs featuring complex cooling channels, however, processing by laser powder bed fusion remains challenging. A comprehensive review by Thomas Niendorf and co‐workers, article number 2100049, is presented providing new insights into the topic by assessing powder‐process–microstructure–property‐defect relationships. Results presented will guide researchers and application engineers.